Simple oxalate precursor route for the preparation of barium-strontium titanate: Ba1-xSrxTiO3 powders - Khollam, Y. B.; Deshpande, S. B.; Potdar, H. S.; Bhoraskar, S. V.; Sainkar, S. R.; Date, Sadgopal K. (Materials Characterization, 2005)
A simple one-step cation-exchange reaction between the stoichiometric solutions of ammonium titanyl oxalate (ATO) and barium hydroxide+strontium nitrate at room temperature (RT) is investigated successfully for the quantitative precipitation of barium-strontium titanyl oxalate (BSTO): Ba1-xSrxTiO(C2O4)(2).4H(2)O (x=0.25) precursor powders with nearly theoretical yield (greater than or equal to99%). The pyrolysis of BSTO at 730degreesC/4 h in air produced barium-strontium titanate (Ba1-xSrxTiO3; BST) powders. The characterization studies on BSTO and BST powders by using various physico-chemical techniques: micro- and chemical analysis, differential thermal analysis (DTA)/thermo-gavimetric analysis (TGA), XRD, FTIR, X-ray fluorescence (XRF) and scanning electron microscopy (SEM) revealed that the powders formed are cubic, highly pure, stoichiometric and sub-micron-sized with nearly uniform size and shape distribution. The ceramic compacts obtained by sintering the BST pellets at 1300degreesC/4 It showed density similar to95%, dielectric constant epsilon(Tc)similar to9500, tan delta-0.15% and T(C)similar to32 degreesC. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: barium-strontium titanate; barium-strontium titanyl oxalate; permittivity; XRF

Synthesis and characterization of microwave-hydrothermally derived Ba1-xSrxTiO3 powders - Deshpande, S. B.; Khollam, Y. B.; Bhoraskar, Y. B.; Date, Sadgopal K.; Sainkara, S. R.; Potdar, H. S. (Materials Letters, 2005)
Submicron-sized, spherical, stoichiometric strontium substituted barium titanate: Ba0.75Sr0.25TiO3 (BST) powders are prepared by microwave-hydrothermal (MH) route under the MH conditions of 200 degreesC, 200 psi, and 30 min in strongly alkaline conditions (pH>12) using potassium titanyl oxalate (KTO) and nitrates of Ba and Sr as the starting precursors and KOH as the mineralizer. The characterization studies by XRD, XRF and SEM indicated that stoichiometric cubic BST powders (a(0)=3.992 A) were obtained by adjusting MH conditions mentioned earlier and keeping the (Ba+Sr)/Ti ratio in starting solution slightly in excess (similar to1.06). (C) 2004 Elsevier B.V. All rights reserved.
Keywords: barium-strontium titanate; dissolution-recrystallization; Microstructure; microwave-hydrothermal synthesis; mineralizer; SEM; XRD; XRF

Synthesis and magnetic properties of polycrystalline Co-doped ZnO - Deka, Sasanka; Date, Sadgopal K.; Joy, Pattayil Alias (9th International Conference on Ferrites (ICF-9), 2005)
Nanocrystalline Zn1-xCoxO powders have been synthesized by a glycine-nitrate (GNP) and modified GNP methods. Ferromagnetism at room temperature and above is observed for the powder samples synthesized by GNP method. The saturation magnetization value at 300 K is obtained as 0.08 and 0.28 emu/g (at 1 T), respectively, for x = 0.05 and 0.1. Ferromagnetic transition occurs at 740 K and 770 K for the respective samples, which is much larger than that the reported in the literature for thin film samples. On the other hand, no ferromagnetism was observed, down to 10 K, for the compounds synthesized by the modified GNP method.

Structure-function mimicry of oxidized purple acid phosphatase-PAP(ox)-A new functional model - Waghmode, Shobha A.; Date, Sadgopal K.; Gupta, Vidya S.; Rane, Sandhya Y. (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2010)
{Electronic structure and spectroscopic properties of the novel diiron active site of oxidized mammalian purple acid phosphatase analogues, Fe-6: [Fe-2 (mu-O) (mu-OAc) (4HNSQ(ox))(2 center dot-)(ONSQ(ox))(2 center dot-)(H2O)(4)] and Fe-7: [Fe-2 (mu-O) (mu-OAc)(ONSQ(ox))(2 center dot-)(OAc) (H2O)(4)] are described. Magnetic susceptibility SQUID data of Fe-6 are best fitted to Heisenberg's isotropic spin pair (S = 5/2, 3/2) model using magnetic parameters g = 2 and J = - 36.8 cm(-1) with R factor = 6.4 x 10(-4). The antiferromagnetic exchange establishes Fe(III)-O-Fe(III) dimeric core with Fe(III) site having two radical ligations in the naphthosemiquinone oxime form of lawsone oxime. In the model compound Fe-7 of oxidized purple acid phosphatase, bridged and terminal acetate functions are identified according to their different energies of activations, i.e, similar to 34 and 58 kJ mol(-1) respectively. Also, the reduced naphthoquinone oxime form of ligand is characterized by its energy of activation (similar to 15 kJ mol(-1)) from pyrolytic reaction. Mossbauer parameters
Keywords: Antiferromagnetic exchange; Bioinorganic chemistry; DNA cleavage; iron; Nuclease activity; PAP(ox) analogues

Synthesis of low coercive BaFe12O19 hexaferrite for microwave applications in low-temperature cofired ceramic - Rane, Vivek A.; Meena, Sher Singh; Gokhale, Suresh P.; Yusuf, S. M.; Phatak, Girish J.; Date, Sadgopal K. (Journal of Electronic Materials, 2013)
Polycrystalline M-type barium hexaferrite (BaFe12O19) samples have been synthesized by solution combustion route at different pH and calcination conditions in order to reduce the coercivity for microwave applications in low-temperature cofired ceramic (LTCC) substrates. Structural, morphological, and magnetic properties of BaFe12O19 were studied by x-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), Raman spectroscopy, vibrating sample magnetometry (VSM), and Mossbauer spectroscopy. The formation of a single-phase hexagonal structure was confirmed by XRD. The Raman spectra reveal all characteristic peaks of BaFe12O19, illustrating the phase purity and crystal lattice symmetry of the synthesized material. Mossbauer spectra illustrate the existence of Fe3+ cations at all five crystallographic lattice sites. The microstructural features observed by FESEM disclose the growth of nanoregime particles into hexagonal platelet particles after calcination at temperatures from 800A degrees C to 1200A degrees C. The VSM results show a lower coercivity (1350 Oe to 3500 Oe) together with reasonably high saturation magnetization (55 emu/g to 60 emu/g) and a high bulk resistivity (> 10(9) Omega-cm) at room temperature. The dependence of magnetic and electrical properties on the preparation and processing conditions is also discussed.
Keywords: Barium hexaferrite; coercivity; LTCC; Mossbauer spectroscopy; Raman spectroscopy